78 Impact of additional call triage time on ems response performance and resource use. (16th April 2018) - Turner, J; Jacques, R
Abstract : Aim: Time based standards have been used as a key performance measure for EMS internationally but can lead to operational behaviours that are not clinically focussed. NHS England tested a new operational model (Dispatch on Disposition) allowing additional call triage time of up to 4 min before starting the response interval clock start. Method: A controlled before and after time series analysis of the intervention implemented in 6 of the 10 regional EMS services. We measured weekly trends in average resource allocation per call and a range of time measures for different call types for 1 year before and 7 months after implementation, and used time series regression models to compare changes between intervention and control sites adjusted for seasonality, call volumes and hours lost at hospital handover. Results: The proportion of emergency calls responded to within 8 min increased by 6.6% in the intervention group. The 95th percentile time from call connecting to EMS and a resource arriving on scene reduced by 9.45 and 166.6 s for life-threatening and emergency calls respectively. There was a statistically significant reduction in average resources allocated per incident of −0.1 for life-threatening calls, −0.06 for emergency and −0.12 for urgent in the intervention group – equivalent to an additional 10 243 whole resources available to respond per week in England. There was no change in service re-contact. Conclusion: Additional call triage time does not lead to a reduction in response time performance, improves efficiency of resource use and is safe for patients. Conflict of interest: None Funding: NHS England.